Impact of Fear of Missing Out on Psychological Well-Being Among Emerging Adulthood Aged Social Media Users - Judithya Anggita Savitri (Department of Psychology, Universitas Negeri Yogyakarta, 2019)
This study aimed to find out the impact of Fear of Missing Out (FoMO) FoMO on psychological well-being especially for social media users at the age of emerging adulthood. This study used a quantitative correlational research. The research was conducted through online questionnaire invloving 400 people obtained through accidental sampling method. The data collected using a fear of missing out (FoMO) scale and a psychological well-being scale that had been modified from Przybylski's FoMO scale and Ryff's Psychological well-being scale. The FoMO scale consists of 15 items with good reliability estimation (α = 0.849) and the psychological well-being scale consists of 45 items with also a good reliability estimation (α = 0.941). The data was analyzed using the simple linear regression. The anlysis revealed that FoMO was able to predict psychological well-being (F=43,753; p=0,000 α 0,05). FoMO can predict psychological well-being with a contribution value of 9,99%. The regression equation line obtained was Y = 154,264 – 0,633X. Further discussion regarding the impact of fear of missing out on psychological well-being among emerging adulthood aged social media users were elaborated.